Distribution and paleoenvironmental framework of middle Miocene marine vertebrates along the western side of the lower Ica Valley (East Pisco Basin, Peru). Issue 2 (1st December 2021) - Collareta, Alberto; Di Celma, Claudio; Bosio, Giulia; Pierantoni, Pietro Paolo; Malinverno, Elisa; Lambert, Olivier; Marx, Felix Georg; Landini, Walter; Urbina, Mario; Bianucci, Giovanni
ABSTRACT: We report 130 vertebrate fossils preserved as bony elements and the co-occurring assemblage of fish teeth and spines from the lower strata of the Pisco Formation exposed along the western side of the lower Ica Valley (East Pisco Basin, Peru). Geological mapping at 1:10, 000 scale reveals that all these fossils originate from the Langhian–Serravallian P0 allomember. In the study area, P0 is up to ∼40 m thick and features a sandy lower portion, reflecting shoreface deposition, that fines upwards into a package of offshore silts. Marine vertebrates only occur in the lower sandy layers and include whales, dolphins, reptiles, birds, and bony and cartilaginous fishes. The reconstructed paleoenvironment is consistent with a warm-water, marginal-marine setting with a strong connection to the open ocean. This work helps to elucidate the rich yet still poorly understood middle Miocene portions of the Pisco Formation, and highlights the need to conserve this outstanding Fossil-Lagerstätte.